The glucose transporter GLUT3 controls T helper 17 cell responses through glycolytic-epigenetic reprogramming - Hochrein, Sophia M.; Wu, Hao; Eckstein, Miriam; Arrigoni, Laura; Herman, Josip S.; Schumacher, Fabian; Gerecke, Christian; Rosenfeldt, Mathias; Gru, Dominic; Kleuser, Burkhard; Gasteiger, Georg; Kastenmu, Wolfgang; et al. (Cell Metabolism, 2022)
Metabolic reprogramming is a hallmark of activated T cells. The switch from oxidative phosphorylation to aerobic glycolysis provides energy and intermediary metabolites for the biosynthesis of macromolecules to support clonal expansion and effector function. Here, we show that glycolytic reprogramming additionally controls inflammatory gene expression via epigenetic remodeling. We found that the glucose transporter GLUT3 is essential for the effector functions of Th17 cells in models of autoimmune colitis and encephalomyelitis. At the molecular level, we show that GLUT3-dependent glucose uptake controls a metabolic-transcriptional circuit that regulates the pathogenicity of Th17 cells. Metabolomic, epigenetic, and transcriptomic analyses linked GLUT3 to mitochondrial glucose oxidation and ACLY-dependent acetyl-CoA generation as a rate-limiting step in the epigenetic regulation of inflammatory gene expression. Our findings are also important from a translational perspective because inhibiting GLUT3-dependent acetyl-CoA generation is a promising metabolic checkpoint to mitigate Th17-cell-mediated inflammatory diseases.
CRIS-Team Scopus Importer:2023-03-23
Keywords: acetyl-CoA; ACLY; ATP-citrate lyase; glucose metabolism; GLUT1; GLUT3; glycolysis; histone acetylation; immunometabolism; Th17 cells